Assessment of Human Resource Distribution and Workforce Challenges in Nepal’s Eye Health Sector: A Mixed-methods Study - Ranjan Shah; Rajiv Ranjan Karn; Lisasha Poudel; Sailesh Kumar Mishra; Sudhir Kumar Thakur; Kalpana Chaudhary; Bandana Paneru; Archana Shrestha; Sandip Das Sanyam; Priya Morjariya; Lalit Agarwal; Chet Raj Pant (Journal of Nepal Medical Association, 2026)
Introduction: Over 2.2 billion people worldwide have vision impairment, mostly in low- and middle-income countries like Nepal. Despite growth in the eye care workforce, Nepal is still facing the challenges in the distribution and management of workforce. This study assessed the distribution, and challenges of the eye care workforce in Nepal. Methods: A convergent, mixed-methods, cross-sectional study was conducted from January-November 2024 across 329 eye health facilities in Nepal. Quantitative component assessed the workforce distribution via an online questionnaire, while qualitative data were gathered through 11 key informant interviews with significant stakeholders to capture insights on multiple strategies and policy challenges within the sector. Descriptive statistics were used for quantitative analysis, and thematic analysis was applied to qualitative data to identify key insights into human resource distribution and challenges in eye care. Results: Among the 329 institutions surveyed, 249 (75.68%) were operated by nonprofit organizations. The national average was 1.49 ophthalmologists per 100,000 population, compared with the recommended benchmark of one ophthalmologist per 100,000 population. Provincial variation was observed, with ratios of 0.18 in Karnali and 0.37 in Sudurpashchim. Key challenges included workforce distribution and optometrist brain drain, highlighting the need for workforce deployment, retention strategies, curriculum reform, and supportive policy interventions. Conclusions: This study highlights a significant gap between production of workforce and their effective deployment across the country. Addressing this gap will require improved workforce distribution, expansion of subspecialty services, balanced workloads, updated training, effective retention strategies, and supportive policy reforms to ensure equitable access to high-quality eye care nationwide.